Taxonomy and nomenclature of Aspidosperma (Apocynaceae) - Devides Castello, Ana Carolina; de Souza Pereira, Andreza Stephanie; Shimizu, Gustavo Hiroaki; Rizzo Zuntini, Alexandre; Olmos Simões, André; Koch, Ingrid (Phytotaxa, 2022)
Aspidosperma is one of the most diverse and economically relevant taxa within Apocynaceae, leading to several taxonomic studies being carried out with the genus. However, since its species number varies widely depending on the treatment, questions regarding which species ought to be recognized in the genus are frequent. We addressed all names and designations in Aspidosperma and proposed 19 new synonyms, six neotypes, 59 lectotypes, and 15 second-step lectotypes. We also created an online interactive identification key for the 80 recognized species of Aspidosperma.